"Biological identikit": Development of a SNPs-panel for the analysis of forensic DNA phenotyping and ancestry. (December 2022) - Sguazzi, Giulia; Varrone, Debora; Cirioni, Chiara; Andrioletti, Valentina; Linarello, Pasquale; Salvaderi, Luca; Lovisolo, Flavia; Procopio, Noemi; Gentile, Fabiano; Cherubini, Anna; Colloca, Domenico; Marino, Alberto; et al.
Abstract: Personal identification in mass disasters and in crimes is essential for humanitarian, ethical and legal reasons. In these contexts, when individuals cannot be identified by standard forensic DNA analysis, the Forensic DNA Phenotyping and the analysis of the biogeographical ancestry could help. The aim of this study was to evaluate the potential of a new panel of 891 SNPs in predicting phenotypic traits and biogeographical origin to create a "biological identikit". In addition to fresh biological material, old evidence found at the crime scene or extracted and long-term stored DNA were tested with 41 SNPs for phenotyping and 850 SNPs for ancestry. All the SNPs were successfully incorporated into a single two-step multiplex PCR reaction using the IonAmpliSeq ™ Library Plus and applied for massive parallel sequencing with the Ion S5 platform using up to 0.05 ng/µL of DNA. The analysis of the results was carried out with an in-house predictive algorithm and consulting 20 population databases. By comparing the results obtained with identikit or video-photographic surveys, it was possible to predict phenotype and ancestry with an accuracy greater than 90%. While these new markers cannot identify a specific individual, they can be a valuable investigative tool.